QUALITY STUDY OF KITIN AND KITOSAN OF KARNAVERSE LOBSTER FRESH WATER (Cherax quadricarinatus) BASED ON MORFOMETRIC LINEN TOBA NORTH SUMATERA PROVINCE - Yoanes Namora Sembiring; Mery Sukmiwati; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe aim of this research was to determine the characteristics of the quality of chitin and chitosan of fresh water lobster (Cherax quadricarinatus) carapace. The method used was an experimental method with a Completely Randomized Design (CRD) which consists of 3 levels of treatment: large morphometric 13-18 cm, moderate morphometrics 7-12 cm and small morphometric 1-6 cm, with 3 replicates. The parameters used were yield, moisture content, chitosan solubility, deacetylation degree, ninhydrine test and organoleptic test.The results showed that the best chitosan quality was obtained in moderate treatment (7 -12 cm) with yield 90.49%, moisture content 6.10%, deacetylation degree 56%, organoleptic test 5.45%, ninhidrine test 0.5129 g. Keywords: chitin and chitosan, carapace, freshwater lobsters, morphometrics, organoleptics, moisture content..